Eksistensi Infotainment dan Respon Masyarakat Muslim : Analisis Persepsi Kualitas Infotainment di Era Digital - Vyki Mazaya; Akhmad Latif (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2024)
The existence of television programs in the digital era is increasingly being questioned due to the emergence of new media.  From data from a survey conducted by KPI (Indonesian Broadcasting Commission) in 2021, there are television programs that are considered not useful, one of which is infotainment. However, infotainment programs still exist and can even be broadcast more than once a day on television. The Muslim community should consume useful and quality broadcasts, but in fact the Muslim community is a contributor to infotainment viewers. This research intends to explain the Muslim community's perception of the quality of infotainment in the digital era. This research is field research which uses a quantitative approach and is analyzed using the SOR (Stimulus-Organism-Response) theory. Data was obtained through questionnaires and documentation. The main data source comes from Muslim communities selected by purposive sampling.  The results of this research showed that the Muslim community regarding the quality of infotainment programs in the information aspect had a positive perception, in the entertainment substance aspect they also had a positive perception, but in the education aspect they had a negative perception. In response to the perception that emerged, it can be said that the Pekalongan Muslim community rarely watches infotainment, the majority only 1-2 times a week. Meanwhile, the viewing duration can also be summed up briefly. In accordance with SOR theory, the stimulus that is perceived as not positive in one aspect, namely education by the viewer, also has an impact on the frequency and duration which is not optimal.